Sistema informático de control de notas y proceso de matriculación de la unidad educativa wenceslao rijavec de la ciudad de calceta - cantón Bolívar - Mora Macías, Nestor Adrián (2013)
The purpose of this research was to create a computer control system of notes and registration to automate the information in an agile, efficient and effective use of students of the Education Unit "Rijavec Wenceslao" (UEWR) Sock City-Canton Bolívar, to the effect development strategy implemented Lifecycle incremental model. He opened up the gathering research information to meet short features the processes performed daily in the institution, as well as determine the physical and functional requirements necessary for the computer system. We used inductive method of scientific inquiry - deductive techniques like interview - observation, which allowed to detect and were brought enrollment processes and control UEWR notes. Creation performed data flow diagram, the use case diagram and relational database. For the development of software technology tools were used Microsoft Visual Studio. NET 2010 and Microsoft SQL Server 2008 R2 together with design programs such as Photoshop CS5 and Win Forms DevComponents which is a component for creating impressive user interface professionally. Subsequently performed validation tests in which it was found that the optimized system control processes notes and UEWR registration of a 73.11% uptime, with reference to the processes that it performed manually. Once confirmed the authors system optimization are terminated a successful work that allowed the Educational Unit "Rijavec Wenceslao" efficiently and effectively improve their educational processes.